2019
DOI: 10.1177/1937586719851266
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Reality to Compare Design Alternatives Using Subjective and Objective Evaluation Methods

Abstract: Objective: This study sought to develop a method that supports a more evidence-based approach to evaluating multiple design options in virtual reality (VR), combining subjective insights gathered using traditional approaches and objective feedback gathered using the VR platform. Additionally, this study sought to understand how objective data garnered from the VR platform could be used to compliment traditional evaluation strategies. Background: VR can be a viable research platform for supporting evidence-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…In design practice, VR can lead to a better decision-making at the early stages of design conceptualization, in particular, when having a design presentation assessment for moderate designs, where at these moments, decision-making has a great effect on the project executions costs (Paes et al, 2017). Hence, previous studies have applied VR to show design alternatives among stakeholders for a single design proposal or for comparing physical environments with virtual environments (VEs) to have stakeholder's unanimity (Wingler et al, 2020). To aid in the decision-making process, accurate perception of the modeled artifacts needs to be made.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In design practice, VR can lead to a better decision-making at the early stages of design conceptualization, in particular, when having a design presentation assessment for moderate designs, where at these moments, decision-making has a great effect on the project executions costs (Paes et al, 2017). Hence, previous studies have applied VR to show design alternatives among stakeholders for a single design proposal or for comparing physical environments with virtual environments (VEs) to have stakeholder's unanimity (Wingler et al, 2020). To aid in the decision-making process, accurate perception of the modeled artifacts needs to be made.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study showed that less time is needed to make a 3D model while being fully immersed in it. Moreover, the study by Wingler et al (2020) showed that evaluations in VR based on simulation are viable in design iterations. The authors recruited 30 participants to test their physical interaction in VEs for three operation rooms in a healthcare institution.…”
Section: Architectural Virtual Reality Modelsmentioning
confidence: 99%
“…The prefabricated buildings or so-called “modular structures” are also being used in emergency therapeutic plans in other parts of the world. For example, the “architecture + health” project of Clemson University in the United States is testing whether it is feasible to connect containers in series to assemble rapid response therapeutic facilities [ 14 ]. It has been commented that the progress of this technology “may be the future of rapid deployment of health care” [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To highlight only a couple healthcare examples, the use of VR has demonstrated effectiveness for use with stroke rehabilitation outcomes [ 14 , 15 ], as well as surgical training to perform a laparoscopy [ 16 ] and bronchoscopy [ 17 ]. VR is also more commonly being used as a tool in architectural design, initially being used in the design of courthouses [ 18 , 19 ], and later for healthcare environments such as hospital patient rooms [ 2 , 6 , 20 , 21 , 22 ], operating rooms [ 5 , 23 ], preoperative rooms [ 24 ], intensive care units [ 19 ], and hospital lobbies [ 18 ]. Many of these previous examples allowed users to perform walkthroughs of the space and provide feedback.…”
Section: Introductionmentioning
confidence: 99%